HUBUNGAN ANTARA REGULASI DIRI DENGAN PENYESUAIAN DIRI REMAJA - Kanzul Atiyah; Abd. Mughni; Nur Ainiyah (Fakultas Dakwah Universitas Ibrahimy, 2020)
Islamic boarding schools are educational institutions that have strong roots in the Muslim community in Indonesia. Being in a boarding school requires students to make adjustments. One factor that influences self-adjustment is self-regulation. This research is a type of correlation research. The data obtained were analyzed using the statistical calculation of product moment correlation. Sampling using proportionate startified random sampling totaling 87 people. The measuring instrument used is a scale of self-regulation that refers to Bandura’s theory and a scale of adjustment that refers to Schneiders theory. The results of this study indicate that the level of self-regulation of adolescent new students is in the high category of 49 students (56%), and as many as 38 students (44%) are in the medium category. The results of the adjustment level of teenage new students were in the high category of 58 students (67%), and 29 students (33%) were in the medium category. The product moment analysis results show that there is a positive and very significant relationship between self-regulation and self-adjustment shown from the results of the Pearson correlation of (r) = 0.424 with sig (p) = 0.000 (p <0.05). The analysis test results show that the higher the level of self-regulation, the higher the adjustment it self